Vaginal microbiota profile at the time of embryo transfer does not affect live birth rate in IVF cycles with donated oocytes. Issue 6 (June 2019) - Vergaro, Paula; Tiscornia, Gustavo; Barragán, Montserrat; García, Désirée; Rodriguez, Amelia; Santaló, Josep; Vassena, Rita
ABSTRACT: Research question: What is the relationship between the vaginal microbiota profile at the time of embryo transfer and live birth rates in women undergoing IVF/intracytoplasmic sperm injection (ICSI) with donated oocytes? Design: One hundred and fifty Caucasian women receiving donated oocytes were prospectively included in the study from March 2017 to January 2018. Samples of vaginal fluid were taken immediately before transfer of a fresh single blastocyst and genomic DNA (gDNA) was extracted. Bacterial load as well as the presence of four lactobacilli ( L. crispatus, L. gasseri, L. jensenii and L. iners ) and species associated with bacterial vaginosis ( Gardnerella vaginalis, Atopobium vaginae, Mycoplasma hominis and Prevotella spp. – here collectively termed BVB) were determined by quantitative polymerase chain reaction. Vaginal microbiota profiles for each patient were characterized and correlated with reproductive results. Results: Although bacterial load was variable, a majority of samples were dominated by a single species (80.7%, 121/150). Most samples (76.7%, 115/150) were dominated by Lactobacillus spp., while 23.3% (35/150) were dominated by bacteria associated with bacterial vaginosis. The distribution of microbiota profiles among women who achieved a live birth and women who did not was similar ( P  = 0.43). Interestingly, we found a significantly higher proportion of samples dominated by L. crispatus - in women achieving live birth compared with those who did not ( P  = 0.021); this correlation was also statistically significant for biochemical pregnancy ( P  = 0.039) and clinical pregnancy ( P  = 0.015). Conclusions: Our data suggest that bacterial vaginosis-like vaginal microbiota at the time of embryo transfer does not directly affect the live birth rate.